De l’énonciation à la méta-énonciation - Jean-Jacques Franckel (Corela)
A metalinguistic discourse can be defined as taking the language as its topic. This article takes another approach based on the analysis of markers or combination of markers which operate as a comment on how what is being said is actually said or should be said in the progressing enunciation.These markers can either be specific and easily localized or not specific but taken in more or less specific combinations which give them this function. Various examples are taken in support of this approach, including those shaping the notions related to the words used to express what is to be said.